(untitled) (Global Journal of Medical Research, 2014)
To study knowledge, attitude and risk factors of Japanese Encephalitis (JE), a research was conducted from May to November 2012 in Rupandehi district Nepal including household (HH) survey, pig survey and swine sero survey. Questionnaire survey on One hundred HH (50 pig raisers and 50 pig non raisers) to compare JE risk factors; 100 pig farmers to study roles of pig as risk factor for JE in human was conducted. Altogether 54% of respondents heard about JE with 60% (30/50) in pig raisers and 48% (24/50) in pig non raisers, which was not significantly different (p> 0.05). The media like Radio, TV, were found the most important source of information. The knowledge of JE was found significantly higher (p